Optimalisasi Tata Kelola Keuangan UMKM melalui Literasi Keuangan Strategis di Desa Balleanging Kabupaten Bulukumba - Nurhaedah Nurhaedah; A. Reski Almaida Dg Macenning; Andi Dewi Angreyani; Muhammad Rijal Alim Rahmat; Indri Iswardhani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the local economy; however, many MSMEs still face challenges in financial management, including inadequate transaction recording and the absence of separation between personal and business finances. This community service activity aimed to improve MSME financial governance through strategic financial literacy in Balleanging, Bulukumba. The activity was conducted at the Balleanging Village Hall on Saturday, July 18, 2026, involving MSME actors as participants. The implementation method consisted of preparation, training, practical financial management activities, and evaluation using pre-test and post-test assessments. The training materials covered business entity separation, simple financial recording, cash flow management, and basic financial decision-making for business operations. The evaluation results showed an increase in participants’ financial literacy levels from 61% before the training to 83% after the training. These findings indicate that strategic financial literacy activities can strengthen MSME actors’ understanding and ability to implement more structured financial governance practices. This program is expected to support business sustainability by encouraging better financial discipline and management practices.